Use Of Interactive Learning Media To Improve Language Capabilities Early Children - Dwi Rulismi (Indonesian Journal of Basic Education, 2022)
This research is based on the changing "Mood" of AUD children, so this is inline with an interactive learning model, in encouraging children's curiosity for knowledge, it is important to know the teacher's strategy in using interactive learning media to improve early childhood language skills, The intended ability includes the ability that children use to communicate, both in the form of writing, speech, body code and sign language. In an effort to reveal the facts from the findings when this research was conducted, the method used in this study was a quantitative method. In its implementation, the sample from this study was tested on a limited scale and also tested on a wide scale. For the limited-scale trial consisting of 2 teachers and 1 class of children in group B1 totaling 15 people, while for the wide-scale test consisting of 2 teachers with 2 classes of children in groups B1 and B2 totaling 30 children. To support the iteration of the required data, this research in the implementation of collecting data uses direct observation and written test. The data analysis technique applied was using the average score, percentage and t-test. It is concluded that the development of interactive multimedia-based teaching materials is feasible to use to improve language skills based on limited and broad tests. And the development model is effective in improving children's language skills